EXTERNAL ECONOMIC ACTIVITY OF SOCIO-ECONOMIC SYSTEMS: STATE, MANAGEMENT AND ASSESSMENT - TYURINA, Nila; NAZARCHUK, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the theoretical and methodological foundations of integrating controlling with digital technologies within the enterprise sustainable development management system. The role of controlling as an instrument for coordinating, planning, analysing, and monitoring the economic, environmental, and social performance indicators of an enterprise is substantiated. The findings of foreign and domestic researchers are summarised, and unresolved issues within the selected research area are identified. A methodological approach to integrating controlling with digital technologies in the context of sustainable development has been developed; it includes diagnosis, target-oriented design, digital integration, performance assessment, and further development. The key directions of digitalising controlling processes using modern technologies—ERP systems, Business Intelligence, big data analytics, artificial intelligence, and the Internet of Things—are determined. A methodological approach to forming a model of digital controlling for sustainable development is proposed, encompassing the stages of diagnosing a company’s digital maturity, defining sustainable development goals, integrating ESG analytical indicators into digital platforms, and assessing the effectiveness of their implementation. The practical effectiveness and adaptability of the model to industry-specific conditions are confirmed using examples from industrial enterprises, the agricultural sector, and the service sector. It is substantiated that the implementation of digital controlling contributes to improving energy efficiency, reducing resource intensity, and fostering corporate social responsibility. It is concluded that digital controlling for sustainable development is an innovative strategic management tool that enhances enterprise competitiveness, ensures business process transparency, and aligns corporate objectives with global sustainable development benchmarks.
Keywords: controlling; management; digital technologies; sustainable development; ESG; digital transformation; Business Intelligence; ERP; data analytics; strategic management